(untitled) (Acta Scientiarum. Biological Sciences, 2015)
Current analysis investigated the tickcide effects of the aqueous extract and chloroform fractions of Ruta graveolens L. (rue) on engorged females of Rhipicephalus microplus, as well as their genotoxic and mutagenic effects on human leukocytes. The best tickcide activity (non-dependent dose) and genotoxic / mutagenic effects (dependent-dose) were observed on exposure to chloroform fractions. Results suggest that extract fractions of R. graveolens L are efficient against R. microplus, although the fraction and the tested concentrations show genotoxic and mutagenic potential for human leukocytes.